A comparison of intramuscular ketamine with high dose intramuscular midazolam with and without intranasal flumazenil in children before suturing. Issue 1 (1st January 2001) - McGlone, R; Fleet, T; Durham, S; Hollis, S
Abstract : Objectives —(a) To compare the use of high dose intramuscular midazolam with and without intranasal flumazenil in children after suturing. (b) To compare the use of high dose intramuscular midazolam with low dose intramuscular ketamine in children before suturing. Methods —87 children, aged between 1 and 7 years, presenting with simple wounds needing sedation, were studied. Children considered combative (n=47) were given ketamine (2.5 mg/kg intramuscularly). The remaining 40 children were given midazolam (0.4 mg/kg intramuscularly) with and without flumazenil (25 μg/kg, intranasally). Results —The median oxygen saturation was 97% in both midazolam groups. Flumazenil significantly reduced the amount of agitation during recovery (p=0.048) and also the time at which children were ready for discharge (median 55 versus 95 minutes, p value <0.001). After discharge both midazolam groups had an unsteady gait (75%) and there was no significant difference in the duration. As expected because of the deliberate selection of combative children into the ketamine group, the pre-sedation behaviour was slightly more disturbed compared with the midazolam group (p=0.10). However, the ketamine group was less agitated during local anaesthetic and suturing p<0.001. Conclusion —Intramuscular midazolam (0.4 mg/kg) did not effectively sedate the children, in that a significant number still had to be restrained. However, none could remember the suturing. Intranasal flumazenil seems to be effective in shortening the time to discharge. If midazolam is to be used then a dose high enough to produce full amnesia should be used, there seems to be no advantage in increasing the dose further. Low dose intramuscular ketamine remains the drug of choice.